Dampak Permintaan Dan Penawaran Pangan Terhadap Ketahanan Pangan Di Sumatera: Pendekatan Panel Kointegrasi - Teapon, Rizal Rahman H; Evalia, Nur Afni (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The purpose of this study is to examine how the relationship between food supply and demand for food security by using a cointegration panel analysis in 10 provinces in Sumatra during the 2011-2019 period. The cointegration panel approach in this study includes the Levin, Lin and Chu Panel Unit Root Test model, Kao Residual Cointegration Test, and Fully Modified OLS Cointegration Panel (FMOLS). The results showed that each variable used in this study had a long-term relationship to food security (food stability), on the other hand, only two variables had a short-term relationship to food security